Buddhism in South East Asia and Swami Vivekananda’s Thought for the West - Panda, Narasingha Charan; (Cherdchai Sīlasampanno), Phrakittisarasuthee (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Buddhism is a religion that was founded by Siddhartha Gautama (The Buddha) more than 2,560 years ago in India. With about 480 million followers, scholars consider Buddhism one of the major world religions. The religion has historically been most prominent in East and Southeast Asia, but its influence is growing in the West. Many Buddhist ideas and philosophies overlap with those of other faiths.